Pattern and management of penetrating and nonpenetrating thoracic injuries - Pal, Naresh; Mishra, Vineet; Jain, Udit; ., Poonam (International Journal of Research in Medical Sciences, 2019)
Background: Chest trauma constitutes a major public health problem which includes the injuries to chest wall, pleura, tracheobronchial tree, lungs, diaphragm, oesophagus, heart and great vessels. It consist of more than ten percent of all traumas and twenty five percent of death due to trauma occurs because of chest injury. Chest trauma is increasing in frequency in urban hospitals. Penetrating and nonpenetrating thoracic injuries the most serious injuries leading to significant morbidity and mortality. Methods: This study was prospective observational study of 220 patients of thoracic trauma both penetrating and non-penetrating. These patients admitted in general surgical units from August 2017 to May 2018 of Pandit Bhagwat Dayal Sharma, PGIMS Rohtak Haryana India. The study was pertaining to both penetrating and non-penetrating chest trauma. Results: Out of 220 chest injury patients who were studied during the said period, Males were 203 and females 17 by a ratio of 12:1 and age ranged from lowest 18 years to 85 years of age. Majority of the patients (90.45%) sustained blunt injuries. RTA was the common mechanism of blunt injury affecting (50.45%) of patients. Multiple Rib fractures was the commonest type of chest injury (21.36%) followed by head injury (17.27%). Head injury was the commonest associated injury seen in our patients. Conclusions: Chest trauma resulting from road traffic accident remains a major mechanism of chest injury. The measures to decrease the trauma are, educating people about traffic rules and regulations and strictly implementing them is necessary to reduce incidence of chest injuries.